Peran Spiritual Dalam Penyembuhan Skizofrenia : A Literature Review - Fadma Aji Pramudita; Iman Permana (Jurnal Keperawatan Muhammadiyah, 2020)
Mental health is one of the health problems in the world, including in Indonesia, one of which is schizophrenia. Management of schizophrenia not only uses pharmacological therapy but also with non-pharmacological therapy. Spirituality is believed to have a role in the treatment of schizophrenia. Purpose: This article aims to identify and analyze research articles about the spiritual role in healing in schizophrenic patients. This article search uses a literature study approach from several ProQuest, Ebsco ScienceDirect databases, and Google Scholar databases, using the keywords "Spiritual OR Spirituality AND Mental disorder OR Mental Illness OR Schizophrenia". Based on the screening process of 509,589 journals, 9 articles were obtained by selecting inclusion criteria. The results obtained are summarized in 2 theme forms including the spiritual role in mental health problems where the importance of health professionals involves the spiritual dimension in health services as well as the spiritual concepts that play a role in handling mental problems; the second theme is about the spiritual role in schizophrenia healing, which is that spiritual can affect active and adaptive coping in schizophrenia patients. Social support activities, age, service satisfaction, spiritual well-being, and symptom severity are identified as aspirators in the quality of life of patients with schizophrenia. Conclusion: Four things that are felt to have a significant effect on healing schizophrenic patients include interactions or therapeutic relationships with health care providers, increased self-awareness of disease, social support, and the use of psychotropic drugs to reduce symptoms that arise.